Searching Meaning in a Rough Place of Education System - Yulius, Martinus Irwan (Forum, 2025)
Education is much more the transferring knowledge; education needs another aspect of educational system which is experiencing knowledge. Based on his research and reflection on educational system, Paulo Freire stated that education is always characterized by ‘banking education’, a top-down education system to transfer knowledge, in which teachers are main subjects who have packages of knowledge and the students are just recipients. He proposed two basic components of education which are praxis and dialogue. Reflecting on those important aspects and experiencing accompaniment of students in their formation time, the writer would like to highlight the importance of praxis and dialogue in education. In conclusion, education is learning to be a fully human by naming the world, discovering opportunities and transforming the world into a better place. There are three main points to achieve that goal. First, praxis is in twofold activities, action and reflection. Second, dialogue comes in the context of communal reflection. Third, education has to reach and nourish self-identity with which students become who they actually are.